2018
DOI: 10.1016/j.scitotenv.2018.04.343
|View full text |Cite
|
Sign up to set email alerts
|

Sampling of suspended particulate matter using particle traps in the Rhône River: Relevance and representativeness for the monitoring of contaminants

Abstract: Monitoring hydrophobic contaminants in surface freshwaters requires measuring contaminant concentrations in the particulate fraction (sediment or suspended particulate matter, SPM) of the water column. Particle traps (PTs) have been recently developed to sample SPM as cost-efficient, easy to operate and time-integrative tools. But the representativeness of SPM collected with PTs is not fully understood, notably in terms of grain size distribution and particulate organic carbon (POC) content, which could both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 37 publications
0
29
0
1
Order By: Relevance
“…Volumetric grain size distribution was analyzed on a CILAS 1190 laser particle size analyzer (range of values: 1 -2 500 pm) according to the ISO 13320 standard method (AFNOR, 2009). Recent investigation on Particle Size Distributions (PSD) in the Rhône River concluded that the usual percentiles d10, d50 or d90 might not be sufficient to describe grain size due to a multimodal shape (Masson et al, 2018). This shape can be modeled as a combination of several homogeneous subpopulations of mixed particles, each following a log-normal distribution.…”
Section: 5grain-size Distribution and Particulate Organic Carbon Amentioning
confidence: 99%
“…Volumetric grain size distribution was analyzed on a CILAS 1190 laser particle size analyzer (range of values: 1 -2 500 pm) according to the ISO 13320 standard method (AFNOR, 2009). Recent investigation on Particle Size Distributions (PSD) in the Rhône River concluded that the usual percentiles d10, d50 or d90 might not be sufficient to describe grain size due to a multimodal shape (Masson et al, 2018). This shape can be modeled as a combination of several homogeneous subpopulations of mixed particles, each following a log-normal distribution.…”
Section: 5grain-size Distribution and Particulate Organic Carbon Amentioning
confidence: 99%
“…This example of a global PSD that includes the entire particle size range was deconvoluted, assuming a mixture of lognormal sub-distributions (e.g. Masson et al, 2018). On the left side of the PSD, a weak lognormal mode was detected in the clay range, but it was negligible in comparison to the silt 25 volume.…”
Section: Particle Size Profilesmentioning
confidence: 99%
“…• Measurements were performed on CRMs to investigate the accuracy of the different devices and highlight the differences between them. Three CRMs were selected in order to accurately represent the ranges of suspended particle size, mostly silt-size [38] • The last step was conducted on a mixture of the samples collected in the Azergues and Arc Rivers to control the proportion of modes and the impact of coarse particles. The mixtures were prepared by weighing dry particles in the following proportions (Azergues/Arc in %): Each sample was homogenized and then split into 4 subsamples before being sent to the different laboratories for PSD analysis.…”
Section: Protocol Of Intercomparisonmentioning
confidence: 99%
“…Analyses of PSD are systematically conducted not only to study the transport of particles but also to improve the interpretation of contaminant concentrations, and they can also be used for transport modeling. For example, the use of different sampling techniques for suspended particle sampling (particle trap and continuous flow centrifugation) leads to a bias in particle size [38]. In the case of large environmental monitoring networks such as the OSR program, PSD analyses are processed by an array of laboratory lasers.…”
Section: Introductionmentioning
confidence: 99%